2016
DOI: 10.1080/17453674.2016.1180577
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-impregnated incision drape and bacterial recolonization in simulated total knee arthroplasty

Abstract: Background and purposeIodine-impregnated incision drapes (IIIDs) are used to prevent surgical site infection (SSI). However, there is some evidence to suggest a potential increase in SSI risk as a result of IIID use, possibly from promotion of skin recolonization. A greater number of viable bacteria in the surgical field of an arthroplasty, and surgery in general, may increase the infection risk. We investigated whether IIID use increases bacterial recolonization compared to no drape use under conditions of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…55 Guidelines: The WHO and CDC do not feel that draping the area of the incision is necessary, based on low quality evidence (weak recommendation). 6,7 There are, however, current studies 5,51,53 which show that draping the area may reduce SSI. Normothermia and oxygenation.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…55 Guidelines: The WHO and CDC do not feel that draping the area of the incision is necessary, based on low quality evidence (weak recommendation). 6,7 There are, however, current studies 5,51,53 which show that draping the area may reduce SSI. Normothermia and oxygenation.…”
Section: -7mentioning
confidence: 99%
“…51 The use of drapes without antiseptic agents has been shown to increase the risk of SSI. 52,53 NICE recommend the use of iodine impregnated drapes, 9 and recent studies support their use. 51,54 Nevertheless, the issue regarding the use of draping the area of the incision in general and the need for draping with bactericidal or bacteriostatic agents remains unresolved.…”
Section: -7mentioning
confidence: 99%
“…Although the length of stay in hospital was the same, the cost was reduced, because the number of SSIs was lower, with an associated reduction in expensive treatments such as debridement and VAC. In a study by Milandt et al [17], it was reported that bacterial recolonization did not increase in patients who underwent bilateral knee arthroscopy. Bilateral surgery is a factor that increases the operation time.…”
Section: Discussionmentioning
confidence: 99%
“…There is debate within the literature as to whether these drapes offer any significant protection against SSI. [10][11][12][13][14][15][16][17] In addition, we did not review skin edge protection devices as these are only used in other surgical disciplines such as the wound protection devices (WPD) used in general surgery. However, there is growing evidence that the incised skin edge harbours bacteria which is not cleared by standard skin preparation or occluded by incision drapes and therefore the importance of decontaminating or occluding the skin edge requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably would be the patient's skin, which can be partially occluded by adhesive plastic dressings, or more importantly the skin edges of the incision which harbour pathogens unable to be cleared by pre-operative antibiotics or standard skin preparation or occluded by adhesive plastics. [10][11][12][13][14][15][16][17][18][19][20] Alternative sources of bacteria include the surgical team, the instruments, the air or the adjunctive equipment such as the c-arm, microscope or robot. [21][22][23][24][25][26][27][28] The Cochrane review of randomised controlled trials by Webster and Alghamdi examined whether plastic adhesive drapes (alone or in combination with either reusable or displosable drapes) lowered the rate of infection in all types of surgery.…”
Section: Introductionmentioning
confidence: 99%